Integration of ICT in education in Latin America: A bibliometric analysis of challenges and innovations - Santillán, Jenniffer Karem Acosta; Barragan, Gloria Angelica Valderrama; Bajaña, Viviana Paola Mendoza; Valderrama, Dessire Amandiz Castro (Journal of Asian Scientific Research, 2025)
The integration of Information and Communication Technologies (ICT) into educational systems in Latin America presents a significant challenge to achieving inclusive, equitable, and adaptive learning environments. Despite advancements in public policies and innovative initiatives, structural barriers persist, such as limited connectivity, inadequate teacher training, and insufficient technological infrastructure particularly in rural areas. The COVID-19 pandemic magnified these disparities and underscored the need to assess ICT’s role in regional education. This study applies a bibliometric approach to examine scientific literature on ICT integration in Latin American education, identifying key challenges, innovations, and emerging trends. A quantitative, descriptive, and retrospective methodology was used, drawing from Scopus and Web of Science, and following the PRISMA protocol. Findings reveal a surge in publications since 2020, with prominent themes including digital literacy, inclusion, and pedagogical transformation. The results stress the importance of critically appropriating technology rather than using it merely as a tool and advocate for policies sensitive to Latin America’s diverse cultural and socioeconomic contexts. This analysis offers evidence-based insights to guide future research and inform educational innovation strategies aimed at social justice and sustainable development.